2013
DOI: 10.17221/105/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genetically modified soya, maize, and rice in vegetarian and healthy food products in Serbia

Abstract: Zdjelar G., Nikolić Z., Vasiljević I., Bajić B., Jovičić D., Ignjatov M., Milošević D. (2013): Detection of genetically modified soya, maize, and rice in vegetarian and healthy food products in Serbia. Czech J. Food Sci., 31: 43-48.The presence of genetic modifications was analysed in a total of 100 samples of non-labelled vegetarian and healthy food products. The basic raw materials in the samples tested comprised maize, soya, and/or rice. The screening of all samples was performed using the primers for CaMV3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
1
14
0
2
Order By: Relevance
“…Ujhelyi et al (2008) showed that out of 251 soy foodstuffs from the Hungarian market, 38% contained RRS. Herzallah (Herzallah, 2012) reported that out of 280 food and feed samples collected in Jordan during 2007e2008, 5.4% contained Bt-176 maize or RRS, whereas a recent report from Serbia (Zdjelar et al, 2013) showed that 8/32 (25%) soy-containing products were positive for RRS during 2009e2010. CaMV 35S, tNOS and soybean lectin were also detected in 6/16 soy-containing products from the United Arab Emirates, indicating the probable presence of RRS (Premanandh et al, 2012).…”
Section: Presence Of Soya Gmos In the Turkish Retail Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…Ujhelyi et al (2008) showed that out of 251 soy foodstuffs from the Hungarian market, 38% contained RRS. Herzallah (Herzallah, 2012) reported that out of 280 food and feed samples collected in Jordan during 2007e2008, 5.4% contained Bt-176 maize or RRS, whereas a recent report from Serbia (Zdjelar et al, 2013) showed that 8/32 (25%) soy-containing products were positive for RRS during 2009e2010. CaMV 35S, tNOS and soybean lectin were also detected in 6/16 soy-containing products from the United Arab Emirates, indicating the probable presence of RRS (Premanandh et al, 2012).…”
Section: Presence Of Soya Gmos In the Turkish Retail Marketmentioning
confidence: 99%
“…But much of this research, especially on soy and maizecontaining products, has focused on the qualitative detection of GM events (Andr eia Z. Dinon, Bosco, & Arisi, 2010;Arun, Yilmaz, & Muratoĝlu, 2013; Bergerov a, Hrn círov a, Stankovsk a, Lopa sovsk a, & Siekel, 2010; Cardarelli, Branquinho, Ferreira, da Cruz, & Gemal, 2005;Elsanhoty, Al-Turki, & Ramadan, 2013;Gürakan, Aydin, & Yilmaz, 2011;Kakihara, Matsufuji, Chino, & Takeda, 2006;Premanandh, Maruthamuthu, Sabbagh, & Al Muhairi, 2012;Zdjelar et al, 2013). The quantitative detection of GM soy events by qPCR has been reported in relatively few countries (Andr eia Zilio Dinon, Treml, de Mello, & Arisi, 2010;Herzallah, 2012;Kim et al, 2013;K€ oppel, van Velsen, Felderer, & Bucher, 2012;Premanandh et al, 2012;Ujhelyi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies in Serbia on imported food products from European Union countries shows none of the products resulted positive in GM testing. This clearly shows, EU made strict regulations upon the GM crops and GM crop based food products [9]. PCR based detection method for the identification of GM in food and feed samples collected from Jordan market ensued 5.2% of positive from 200 food and 80 feed samples [6].…”
Section: Introductionmentioning
confidence: 96%
“…As mentioned previously, some countries around the world has accepted the GMO products with various limitations like proper labeling. In order to ensure the validity of the available products in the markets, various governmental organizations conduct the screening measures at regular intervals [4][5][6][7][8][9] SYBR green-based real time PCR method was used to detect the GMO food products in markets of Kuwait shown positive results, indicating the need of stringent rules and regulations in order to protect the consumer right's [5][6][7]. LightCycler-GMO screening kit based method was utilized to identify the positive GMO products sold in Saudi Arabia markets which indicates nearly 10% of them are GMO products.…”
Section: Introductionmentioning
confidence: 99%
“…Different varieties of polymerase chain reactions are commonly used for monitoring of GMOs in foods and animal feeds (Shin et al, 2013;Kim et al, 2014;Meriç et al, 2014;Datukishvili et al, 2015;Turkec et al, 2016). Nowadays real-time PCR (qPCR) has become a gold standard in the routine analysis of GMOs, allowing very sensitive detection and especially quantification of GMOs in test samples (Dörries et al, 2010;Elsanhoty et al, 2013;Özgen Arun et al, 2013, Zdjelar et al, 2013Fernandes et al, 2014;Kim et al, 2014;SantaMaria et al, 2014;Turkec et al, 2016). However, to quantify GMO content using qPCR, it is necessary to plot standard curves for both the reference gene and transgen, using serial dilutions of DNA extracted from the reference material, which is time-consuming.…”
Section: Introductionmentioning
confidence: 99%